Kajian Identifikasi Kerentanan Dan Kapasitas Adaptif Masyarakat Kampung Nelayan Tegalsari Dalam Menghadapi Ancaman Kebakaran - Dadi Rusdiana; Syahyudes Rina; Ida Hamida; Larasati Dinda Ayu Pangesti; Novi Dhiya Suryani (JURNAL LITBANG KOTA PEKALONGAN, 2026)
The fishermen’s village of Tegalsari, the City of Tegal, is located on the banks of the Sibelis River. Tegalsari Village is a moderate slum area with various adverse impacts. The increasing Population can influence need for land to accommodate settlement activities. Built-up areas and economic activities can increase the vulnerability of an area to fire disaster. Previously in November 2021, there was a fire disaster at Tegalsari and it took about 72 hours per fire incident to extinguish the flames from the two fires. If taken a look at the frequency of fire hazard and the relatively long time to extinguish fires and caused huge losses, the surrounding community needs to be equipped with the ability to adapt to the vulnerability that they experienced. The aims of this study are to examine vulnerability and adaptive capacity of the people in Tegalsari Fishermen’s Village in dealing with the hazard of fire disaster. The study employs a mixed-method approach, incorporating both quantitative and qualitative methods. The results show that Tegalsari Fishermen’s Village has a high vulnerability area of 47%, medium vulnerability of 27%, and low vulnerability of 26%. Meanwhile, the current condition of the adaptive capacity of the people is relatively low due to a lack of knowledge regarding the vulnerability of the area to the hazard of fire that can occur anytime. The efforts that can be made to increase the adaptive capacity of the people are by increasing knowledge and improving facilities and infrastructure.